2022
DOI: 10.5606/tgkdc.dergisi.2022.23157
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on adult cardiac surgery

Abstract: Bu çalışmada Litvanya'daki bir kalp cerrahisi merkezinde yeni koronavirüs hastalığı 2019 (COVID-19) pandemisinin kalp cerrahisi üzerindeki etkisi araştırıldı. Ça lış m a pla nı: Kasım 2018 -Mart 2021 tarihleri arasında, pandemi sırasında ameliyat edilen erkek COVID-19 negatif hastaların verileri (n=81; ort. yaş: 65.5±8.5 yıl; dağılım, 46-87 yıl), aynı dönemde ameliyat edilen erkek COVID-19 pozitif hastaların verileri (n=14; ort. yaş: 65.2±10.6 yıl) ile karşılaştırıldı. Ayrıca pandemi öncesi (2018/2019; kontrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Fatality rate in patients who had COVID-19 after CVSI was also higher and quite similar with the Aksu et al's[ 6 ] study in aforementioned studies. [ 11 - 13 ] The lower mortality rate reported in the Venckus et al's[ 7 ] study could be related to the usage of remdesivir in most of the patients probably early in the infection in that study. In a double-blind, prospective, randomized, placebo-controlled study, a three days course of remdesivir was shown to reduce the risk of death and hospitalization by 87% among patients with mild COVID-19 and who were at high risk for COVID-19 progression.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Fatality rate in patients who had COVID-19 after CVSI was also higher and quite similar with the Aksu et al's[ 6 ] study in aforementioned studies. [ 11 - 13 ] The lower mortality rate reported in the Venckus et al's[ 7 ] study could be related to the usage of remdesivir in most of the patients probably early in the infection in that study. In a double-blind, prospective, randomized, placebo-controlled study, a three days course of remdesivir was shown to reduce the risk of death and hospitalization by 87% among patients with mild COVID-19 and who were at high risk for COVID-19 progression.…”
Section: Introductionmentioning
confidence: 69%
“…In this issue of the Turkish Journal of Thoracic and Cardiovascular Surgery, Aksu et al[ 6 ] and Venckus et al[ 7 ] reported consequences of having perioperative COVID-19 in patients undergoing CVSI. In both of the studies comparing patients without postoperative COVID-19 infection, patients who developed COVID-19 after CVSI had higher risks of longer hospitalization, resternotomy for bleeding, wound infection, pneumonia, and fatality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations